Development of an electronic vehicular traffic signal controller (Journal of Science and Technology, 2016)
This paper presents the design, construction, and test of an electronic signal controller for urban vehicular traffic control. The design is based on a series of fixed-time signal plans for different time zones of the day and can accommodate sixty-four signal plans. Finite state machine concept was used in the design of the signal controller and the implementation carried out using Large Scale Integrated (LSI) devices. The controller is driven by a real-time clock and can be configured for a six-phase intersection.